Kesejahteraan subjektif online dan masalah privasi terhadap kelelahan menggunakan media sosial - Alfia Hidayatul Hafiza; Adhyatman Prabowo; Silfiasari Silfiasari (Cognicia, 2022)
The fatigue of social media after use is the impact from a person’s lower level of well-being related to their social media life. Social media use can’t be separated from the existence of privacy concerns that can make someone feel physique and mentally exhausted because of their personal information pressure on social media. This study aims to empirically examine the effect of online subjective well-being and privacy concern to social media fatigue. The subjects of this study were social media users aged 20-30 years old, had at least 2 accounts, and used social media with a minimum duration of 6 hours a day, total respondents were 337 and used random sampling technique. The data was collected online using the Online Subjective Well-Being (OSWB), Social Media Fatigue (SMF), and Privacy Concern (PC) scales. Regression analysis showed that online subjective well-being and privacy concerns had an effect on social media fatigue (p<0.001). Keyword: Online subjective well-being, privacy concern, social media fatigue